The genome sequence of the Beautiful Golden Y, Autographa pulchrina (Haworth, 1809) [version 1; peer review: 2 approved] - Douglas Boyes; Kaouthar Eljounaidi (Wellcome Open Research)
We present a genome assembly from an individual female Autographa pulchrina (the Beautiful Golden Y; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 426.2 megabases in span. Most of the assembly is scaffolded into 32 chromosomal pseudomolecules, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 15.25 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,916 protein coding genes.